Pengaruh Kinerja Perusahaan terhadap Kebutuhan Modal Kerja Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia - Eka Putra Pratama; Arif Darmawan (Journal of Applied Accounting and Taxation, 2018)
This study aims to determine the effect of company performance proxied with ROA, Sales Growth, Firm Size, Firm Age, Assets Tangibility, Operating Cash Flow and Leverage to Working Capital Needs (WCR). The data used are secondary data of manufacturing companies listed in Indonesia Stock Exchange (IDX) period 2012-2015. Sampling method using purposive sampling technique. The analysis used is descriptive statistic, panel data regression. Result of research found ROA have a significant positive effect to working capital requirement. Firm Size, Assets Tangibility, and Leverage have a significant negative effect on working capital requirement. Sales Growth, Firm Age, and Operating Cash Flow have no effect on working capital requirement. This research can be used as a consideration of the company to further improve the performance of the company and pay attention to the factors of determination of working capital needs, so that the working capital needs of the company can be fulfilled and optimal.